The application of integrated environmental management to improve storm water quality and reduce marine pollution at Jeffreys Bay (South Africa) - Seebach, Rudi Dieter (Rhodes University, Faculty of Science, Department of Environmental Science, 2006)
It is projected that by 2025 three-quarters of the world's population will live in the coastal zone. This is an alarming statistic, with a consequently significant impact on small coastal towns and the adjacent marine environments. Developing communities within the coastal zone of South Africa have proved to be a significant pollution source of storm water. Studies have shown that storm water that is deposited in the ocean will be trapped in the near shore marine environment causing poor seawater quality over a large distance. Furthermore, this can pose a significant threat to the health of recreational users and important marine ecosystems. In Jeffreys Bay storm water quality is thought to pose a threat to the maintenance of the international Blue Flag status for its beach. The aim of the current project was to investigate the main sources of storm water and subsequent marine pollution at Jeffreys Bay and to develop an appropriate management strategy using the integrated environmental management framework. In order to achieve this objective, it was also necessary to determine the current quality of water at various points within the catchment and near shore marine environment. Even though the storm water was found to be severely contaminated no evidence existed for a negative impact on the marine environment. None the less, a precautionary approach was adopted and a risk assessment employed in order to consider potential impacts on the marine and aquatic environment, human health and socio-economic welfare within the town. Significant sources of storm water contamination included grey water, domestic solid waste disposal and informal ablution. These significant aspects were investigated further and it was found that solid waste management in the catchment was poor with significant quantities of waste, primarily (76%) from domestic sources, being disposed of illegally. A study of sanitation management showed inadequacies where up to 58% of the residents from the informal settlements disposed of their grey water into open spaces. The ratio of residents to toilets in these areas was 28:1, therefore supporting the outcome of the risk assessment. Due to the fact that all the significant aspects were related to anthropogenic waste, an integrated waste management plan (IWMP) was developed that would not only facilitate the reduction of pollution of storm water, but would also allow for sustainable community-based development.
Keywords: Marine pollution -- South Africa -- Jeffreys Bay; Storm sewers -- South Africa -- Jeffreys Bay; Marine ecology -- South Africa -- Jeffreys Bay; Environmental management -- South Africa -- Jeffreys Bay; Environmental risk assessment -- South Africa -- Jeffreys Bay; Community development -- South Africa -- Jeffreys Bay; Sustainable development -- South Africa -- Jeffreys Bay; Sewage disposal -- South Africa -- Jeffreys Bay